Factors Affecting Intention to Write Negative Electronic Word of Mouth (NEWOM) : A Meta-Analysis - Kunja, Sambashiva Rao; Rout, Lisma; Mogili, Ramanjaneyulu; Acharyulu, G. V. R. K. (Indian Journal of Marketing, 2024)
Purpose : The study examined the factors affecting customer intention to write a negative electronic word of mouth (NEWOM) online by synthesizing results from previous studies. More specifically, the study applied meta-analysis to investigate the number of studies conducted on various factors affecting NEWOM. Methodology/Approach : To conduct meta-analysis, this study collected data from various scientific databases such as Scopus, ProQuest, Google Scholar, and EBSCO. After filtering the original 161 articles found by the search according to the effect size of NEWOM associations, the study found the 22 most pertinent research papers for the analysis. Based on the discovered papers, negative emotions such as wrath, remorse, desire for retribution, severity of failure, and frustration were found to be predictive of NEWOM. Findings : The results of the meta-analysis showed that regret, the degree of failure, the desire for retribution, frustration, rage, and negative emotion variables significantly and favorably affected NEWOM. Practical Implications : The findings of the research have some practical and theoretical implications. Practically, managers could leverage findings to understand consumers’ NEWOM behavior and develop better marketing activities. Theoretically, meta-analysis advanced the knowledge of the NEWOM concept and provided significant research directions for future researchers. Originality/Value : The research examined the literature and created a meta-analytical model to examine the factors influencing people’s intent to disseminate NEWOM in contrast to earlier studies on the topic.